Direct Midline Diastema Closure with Composite Layering Technique: A One-Year Follow-Up - KORKUT, BORA; TAĞTEKİN, DİLEK; YANIKOĞLU, FUNDA (HINDAWI LTD, 2016)
Objective. Maxillary anterior spacing is a common aesthetic complaint of patients. Midline diastema has a multifactorial etiology such as labial frenulum, microdontia, mesiodens, peg-shaped lateral incisors, agenesis, cysts, habits such as finger sucking, tongue thrusting, or lip sucking, dental malformations, genetics, proclinations, dental-skeletal discrepancies, and imperfect coalescence of interdental septum. Appropriate technique and material for effective treatment are based on time, physical, psychological, and economical limitations. Direct composite resins in diastema cases allow dentist and patient complete control of these limitations and formation of natural smile. Clinical Considerations. In this case report a maxillary midline diastema was closed with direct composite resin restorations in one appointment without any preparation. One bottle total etch adhesive was used and translucent/opaque composite resin shades were layered on mesial surfaces of the teeth that were isolated with rubber dam and Teflon bands. Finishing and polishing procedures were achieved by using polishing discs. Patient was informed for recalls for every 6 months. Conclusions. At one-year recall no sensitivities, discolorations, or fractures were detected on teeth and restorations. Direct composite resins seemed to be highly aesthetic and durable restorations that can satisfy patients as under the conditions of case presented.
Keywords: CLINICAL-EVALUATION; RESTORATIONS; PORCELAIN; COLOR